The Paradox of Medical Purpose in Genital Modification Practices: The Cases of Italy and France (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
Through a comparison between Italy and France, the article addresses a common interpretation of the notion of health as the first component of the foundation of the medical act which finds a series of problems in the relationship with the second component, i.e. the patient's consent. These critical issues include both the exclusion of consent and excessive appreciation of the same, with paralyzing effects on the protection of health and, conversely, on the stability of the principle of inviolability of the human body. This analysis reveals how such a problematic interpretation leads to an unreasonable normative distinction between female genital mutilation, ethnic circumcision, interventions for the treatment of Sexual Development Disorders and genital cosmetic surgery.
Keywords: medical act; health; female genital mutilation; circumcision; genital cosmetic surgery; Sexual Development Disorders